Corrosion rates of green novel hybrid conversion coating on aluminium 6061 (2020)
The use of chromate conversion coatings have been limited by several protocols as a result of their carcinogenicity and toxicity towards humans and the environment. Searches are ongoing for chromate replacement in coating baths and processes. This paper describes the comparison among the corrosion rates of a novel hybrid conversion coating derived from water extracts of hibiscus sabdariffa calyx in conjunction with ammonium molybdate, a molybdate conversion coating and the so-called chromate conversion coating. Potentiodynamic polarization measurement in 3.5 wt% sodium chloride solution was employed in ranking the coatings as sabdariffa molybdate being more corrosion resistant than chromate, which in turn out performed molybdate.